Alloimmunisation and nephropathy in sickle cell disease patients in Jeddah, Saudi Arabia. (August 2017) - Adam, S.; Badawi, M.
Abstract : Background and Objective: Sickle cell disease (SCD) is a chronic disease associated with a myriad of complications including pain and vaso‐occlusive manifestations. Transfusion is the mainstay of management of SCD‐related complications. However, side‐effects including alloimmunisation may develop and affect disease outcomes. Marked phenotypic heterogeneity of blood donors and recipients increases the risk of alloimmunisation. We report on the prevalence and clinical complications associated with alloimmunisation among patients with SCD in Jeddah, Saudi Arabia. Materials and Methods: Medical records of patients with SCD were reviewed for clinical data including transfusion history. Demographic and clinical variables were compared between alloimmunised and non‐alloimmunised patients. Results: A total of 219 patients with SCD were enroled with a mean age of 24·8 years, and 52·5% (115) were males. Thirty‐nine patients (17·8%) developed alloantibodies at a mean age of 18·4 years, and anti‐E was the most common antibody (18·8%), followed by anti‐K (12·5%). Patients received a mean of 17·27 units of transfusion before developing alloantibodies. Mortality was not significantly different between both groups ( P = 0·562). Alloimmunised patients were older ( P = 0·042) and more females than males developed alloantibodies (69·2% vs. 30·8%, P = 0·003). Further, there was a significant association with severe proteinuria, a marker of SCD nephropathy ( P = 0·015). Conclusion: Despite the ethnic diversity of our donor population, the prevalence of alloimmunisation is comparable to previous reports. Alloimmunisation was associated with severe proteinuria, a marker of SCD nephropathy. Prospective research is needed to further characterise factors associated with risk of alloimmunisation in SCD in Saudi Arabia.